The transition of Nyabong from cultural identity to illegal economy in Sarawak, Malaysia - Parveen, Kaur (Publications International Lahore, Pakistan, 2018)
Nyabong or cockfighting has been a traditional practice among the Ibans in Sarawak, Malaysia. However, vast changes have taken place in this practice to-date. It has been a favourite past- time hobby of the Ibans since the 1800s but has emerged as a social evil lately. Nevertheless, the innovations in this practice have led to its sustainability as an illegal globalised income generating activity often at the expense of cruelty on the cockerels. This study seeks to find the extent of this practice as a source of business and the types of innovations evolved. Purposive sampling research method was used where the game players were interviewed and observations made. It was found that cockfighting has become a major business for many players. They are also involved in illegal cock trafficking from Thailand and Indonesia. It is now practiced in secretive places with heavy bets placed on the lives of these poor cockerels. The government law enforcing agencies regularly crack-down their dens and rings. This study recommends stricter laws imposed on this illegal business to stop this cruel innovation of business sustainability.